PRINSIP GESTALT PADA KOMPOSISI VISUAL POSTER œANCAMAN PENYAKIT SAAT MUSIM HUJAN PRODUKSI DINAS KESEHATAN PROVINSI SUMATERA SELATAN - Mubarat, Husni; Ilhaq, Muhsin; Al Hafids, Abdul Raihan; Fajri, Ahmad Istiqlal (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2023)
Posters are an effective communication medium in conveying information, especially related to public health. This study explores how a poster produced by the South Sumatra Health Service, entitled